2015
DOI: 10.1073/pnas.1423278112
|View full text |Cite
|
Sign up to set email alerts
|

VEGFR3 does not sustain retinal angiogenesis without VEGFR2

Abstract: Angiogenesis, the formation of new blood vessels, is regulated by vascular endothelial growth factors (VEGFs) and their receptors (VEGFRs). VEGFR2 is abundant in the tip cells of angiogenic sprouts, where VEGF/VEGFR2 functions upstream of the delta-like ligand 4 (DLL4)/Notch signal transduction pathway. VEGFR3 is expressed in all endothelia and is indispensable for angiogenesis during early embryonic development. In adults, VEGFR3 is expressed in angiogenic blood vessels and some fenestrated endothelia. VEGFR3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

13
103
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 114 publications
(116 citation statements)
references
References 40 publications
13
103
0
Order By: Relevance
“…Of particular interest, increased Dll4 was observed in VEGF-R2-deficient mouse endothelium after Notch inhibition, suggesting that one or more additional factor(s) is or are involved (Zarkada et al, 2015). This is consistent with the independent action of CCN1 on the activation of Dll4/Notch signaling.…”
Section: Discussionsupporting
confidence: 70%
See 1 more Smart Citation
“…Of particular interest, increased Dll4 was observed in VEGF-R2-deficient mouse endothelium after Notch inhibition, suggesting that one or more additional factor(s) is or are involved (Zarkada et al, 2015). This is consistent with the independent action of CCN1 on the activation of Dll4/Notch signaling.…”
Section: Discussionsupporting
confidence: 70%
“…The same study emphasized a rather important role of VEGF-R3 in the regulation of sprouting of ECs with low Notch signaling activity. Another study by Zarkada et al demonstrated that genetic ablation of VEGF-R2 alone or in combination with VEGF-R3 prevented the increase of vascular density induced by Notch activation, suggesting that VEGF-R2 but not VEGF-R3 is required for the hypersprouting that occurred in the absence of Notch activation (Zarkada et al, 2015). In the same study, VEGF-R2 was required independently of VEGF-R3 for endothelial Dll4 upregulation and angiogenic sprouting, and for VEGF-R3 function in angiogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…There are many studies on the biological function and intracellular signal transduction mechanism of VEGF and its receptors in tumour angiogenesis (Rivera & Bergers 2015), and the possibility of promoting some tumour metastasis (Yang et al 2015;Zarkada et al 2015). The biological activity of VEGF is mainly regulated by two tyrosine kinase receptors of VEGFR-1 (Flt-1) and VEGFR-2 (KDR/Flk-1).…”
Section: Discussionmentioning
confidence: 99%
“…In adults, VEGFR3 is expressed in angiogenic blood vessels and some fenestrated endothelia. VEGFR2 is required independently of VEGFR3 for endothelial DLL4 up-regulation and angiogenic sprouting, and for VEGFR3 functions in angiogenesis [21].…”
Section: Vegf Protein Family and Its Receptorsmentioning
confidence: 99%